2022
DOI: 10.3390/polym14194027
|View full text |Cite
|
Sign up to set email alerts
|

Development of Clinical Weekly-Dose Teriparatide Acetate Encapsulated Dissolving Microneedle Patch for Efficient Treatment of Osteoporosis

Abstract: Teriparatide acetate (TA), which directly promotes bone formation, is subcutaneously injected to treat osteoporosis. In this study, TA with a once-weekly administration regimen was loaded on dissolving microneedles (DMNs) to effectively deliver it to the systemic circulation via the transdermal route. TA activity reduction during the drying process of various TA polymer solutions formulated with hyaluronic acid and trehalose was monitored and homogeneities were assessed. TA-DMN patches fabricated using centrif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…The addition of trehalose to the formulation considerably improved the drug stability. Furthermore, the needles rapidly delivered 87.6% of the drug into porcine skin after 5 min [ 213 ]. An investigation by Zhou et al demonstrated the successful fabrication of dissolving microneedles from a natural material (Bletilla striata polysaccharide).…”
Section: Microneedle Types For Biopharmaceutical Deliverymentioning
confidence: 99%
“…The addition of trehalose to the formulation considerably improved the drug stability. Furthermore, the needles rapidly delivered 87.6% of the drug into porcine skin after 5 min [ 213 ]. An investigation by Zhou et al demonstrated the successful fabrication of dissolving microneedles from a natural material (Bletilla striata polysaccharide).…”
Section: Microneedle Types For Biopharmaceutical Deliverymentioning
confidence: 99%
“…Therefore, a series of experiments on oral delivery of PTH or long‐acting and slow‐released preparation is being carried out. Including a weekly dose teriparatide encapsulated dissolving microneedle patch, 247 an orally available enteric‐microencapsulated teriparatide‐deoxycholic acid nanocomplex, 248 a triple padlock nanocarrier prepared by a taurocholic acid‐conjugated chondroitin sulfate, 249 and an oleic acid‐based dispersion in combination with chitosan‐teriparatide polyelectrolyte complex, 250 whose efficacy needs further verification.…”
Section: Anti‐osteoporosis Therapiesmentioning
confidence: 99%
“…Undeniably, during the preparation, processes such as drying, may increase the drug loss and reduce the efficacy of the drugs. To maintain the stability, Jeeho Sim et al 87 added trehalose to the HA MNs loaded with teriparatide to form bonds with protein drugs, thus slowing down the protein dynamics. After adding 10% trehalose, the activity of the drugs increases to 75.4 AE 8.3% while the activity is only 59.0 AE 3.6% in the control group.…”
Section: Osteoporosismentioning
confidence: 99%